Constrictive bronchiolitis and paraneoplastic pemphigus caused by unicentric Castleman disease in a young woman: a case report - Chen, Ruxuan; Teng, Yaqun; Xiao, Yinbo; Zhang, Lu; Han, Xianlin; Wang, Weibin; Lu, Zhaohui; Tian, Xinlun (Frontiers in Medicine, 2024)
Introduction Constrictive bronchiolitis is a rare and severe condition characterized by progressive and irreversible obstruction of small airways. Constrictive bronchiolitis could be part of paraneoplastic autoimmune multiorgan syndrome secondary to Castleman disease. Case description A 20-year-old female presented with progressive exertional dyspnea and severe obstructive ventilatory dysfunction. She also experienced recurrent and painful oral mucosal erosions. Upon investigation for underlying conditions, contrast-enhanced CT imaging revealed a pelvic mass exhibiting marked enhancement and hypertrophied vessels. A diagnosis of Castleman disease was confirmed via ultrasound-guided percutaneous biopsy of the pelvic tumor. Autoantibodies indicative of paraneoplastic pemphigus were detected using indirect immunofluorescence on rat bladder tissue. Complete surgical resection of the pelvic mass was undertaken with the collaborative efforts of a multidisciplinary team. Despite resolution of mucocutaneous lesions, symptoms of constrictive bronchiolitis persisted after the surgery. Subsequently, the patient underwent lung transplantation and demonstrated significant improvement in lung function. Conclusion Timely diagnosis and comprehensive multidisciplinary management of this rare and life-threatening syndrome are crucial for enhancing patient outcomes.